PORTAL WEB TRAFIK DENGAN METODE SQUID SEBAGAI UPAYA PENCAPAIAN PELAKSANAAN UU PORNOGRAFI DAN PORNOAKSI - SP. Hariningsih.; M.F. lrma Defega (JURNAL DIAN, 2011)
Sguid is one of the open Source application that combines the security and completeness of the facilities to be used a proxy server, squid is not only to use as firewall, but it can be used to used to user authentication, block of the sites and web caching. Therefore the mechanism to protect is used as proxy server. Proxy server requires maintenance and monitoring for hard drive so it is not overload. it is to conform with the existing lnternet traffic conditions and also face the possibilities that may not have been unthinkable at the time of designing the proxy server. other than that for network servers that come with Squid requires the number of very large capacity hard drive, because every page of the request,by the user are stored in the server. Therefore squid server admin have to do maintenance at least once a week for clien that of 10 clients in each network.The experimen result shows that the user can not access the content of pornography. the using of squid method inside the proxy server. The "PORN" content and the user can save the money. The squid is a open source application, it is more useful then another commercial software proxy licenses are expensive.Key Word : Proxy, Squit, Chace, Network Address Translation